Byzantine Vlachs on the “Blue Danube” in the 12th century: stabilization and aspirations - Dudek, Jarosław (Balcanica Posnaniensia. Acta et studia, 2022)
Byzantine Vlachs on the “Blue Danube” in the 12th century: stabilization and aspirations. In the 12th century peace was regained in the Byzantine frontier on the lower Danube. Gradually the invasions of militant tribes from Pontic steppes (Pechenegs, Uzes, Cumans) ceased. Internal unrest among the people of Paristrion also died down. The economic boom strengthened the potential of the local elite. After the liquidation of the Pecheneg’s organization and the process of byzantization of the Bulgarian aristocracy, the importance of the local Vlachs increased. However, their leaders, despite their unquestionable contributions to the Byzantine state, did not have the opportunity to join its elite.